POTENSI DAN PENGEMBANGAN SEKTOR PERTANIAN DI DESA LUBA DUSUN II, KECAMATAN LEMBUR, KABUPATEN ALOR - Novriani Kristin Mautang; Onarita Lanoni; Mita Felisdianti Laana; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to analyse the potential of the agricultural sector in Luba Village, Dusun II, and to identify development strategies with a view to improving the welfare of the community. The methods employed include field observations, interviews with village officials, and the collection of secondary data from village profiles and relevant agencies. The research findings indicate that Luba Village, Dusun II possesses significant agricultural potential, particularly in food crops, horticulture, and smallholder plantations. The availability of fertile land, favourable climatic conditions, and the local community’s knowledge are the main supporting factors in the development of the agricultural sector. However, agricultural development in this village still faces several constraints, such as limited access to technology, a lack of irrigation facilities, and low utilisation of modern agricultural innovations. Based on the analysis, a development strategy is required that encompasses capacity building for farmers, optimisation of land use, strengthening of farmers’ group institutions, and government support in the form of extension services and production input assistance. This study is expected to serve as a foundation for more effective and sustainable agricultural development planning in Luba Village, Dusun II.